2017
DOI: 10.1002/hbm.23633
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of fine‐grained meaning distinctions: An fMRI investigation of scalar quantifiers

Abstract: Communication involves successfully deriving a speaker's meaning beyond the literal expression. Using fMRI, it was investigated how the listener's brain realizes distinctions between enrichment-based meanings and literal semantic meanings. The neural patterns of the Mandarin scalar quantifier you-de (similar to some in English) which implies the meanings not all and not most via scalar enrichment, with the specific quantifier shao-shu-de (similar to less than half in English) which lexico-semantically encodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
(109 reference statements)
1
2
0
Order By: Relevance
“…Therefore, this study uses declarative clauses and tests whether ERPs at several sentence positions can be explained in terms of comprehenders’ expectations of incoming lexical material. By comparing previous results from the quantifier all with the present results from the quantifier some , the current study also adds to recent considerations about the on‐line processing of semantic and pragmatic aspects of quantificational meaning (Zhan, Jiang, Politzer‐Ahles, & Zhou, ).…”
Section: Motivation Of Our Design and Predictions Of A Probabilistic supporting
confidence: 70%
“…Therefore, this study uses declarative clauses and tests whether ERPs at several sentence positions can be explained in terms of comprehenders’ expectations of incoming lexical material. By comparing previous results from the quantifier all with the present results from the quantifier some , the current study also adds to recent considerations about the on‐line processing of semantic and pragmatic aspects of quantificational meaning (Zhan, Jiang, Politzer‐Ahles, & Zhou, ).…”
Section: Motivation Of Our Design and Predictions Of A Probabilistic supporting
confidence: 70%
“…Such findings have been taken as evidence that pragmatic and semantic processing engender qualitatively different brain responses, a claim which has also drawn support from haemodynamic brain imaging research that has found activation in different brain regions for putatively pragmatic versus semantic violations in a similar paradigm (Shetreet, Chierchia, & Gaab, 2014a,b,c;Zhan, Jiang, Politzer-Ahles, & Zhou, 2017). Such a dissociation would be theoretically important, given that it is an open question whether scalar implicatures are derived by pragmatic and semantic mechanisms, as discussed above.…”
Section: Differences Between Pragmatic and Semantic Processingmentioning
confidence: 89%
“…These processes have long been researched in philosophy and linguistics, but only in recent decades has it become a field of research in neuroscience known as “Neuropragmatics” ( Bambini et al, 2011 , Bara et al, 1997 , Cutica et al, 2006 , Gambi et al, 2015 , Hagoort and Levinson, 2014 , Levinson, 2016 , Noveck, 2018 , Sauerland and Schumacher, 2016 , Soroker et al, 2005 ). Substantial linguistic and neurocognitive research has focused on cases where pragmatic processing is most pronounced, that is, in non-literal meanings, including indirect speech, metaphors, irony and humour ( Bambini et al, 2011 , Bambini et al, 2019 , Boux et al, 2022 , Canal and Bambini, 2020 , Coulson, 2008 , Eviatar and Just, 2006 ), on the study of Gricean conversational implicatures ( Benz and Gotzner, 2021 , Degen and Tanenhaus, 2011 , Feng et al, 2021 , Gotzner et al, 2018 , Hartshorne et al, 2015 , Noveck and Posada, 2003 , Zhan et al, 2017 ) or addressing social and pragmatic deficits in various clinical populations ( Bambini et al, 2022 , Baron-Cohen, 1988 , Carotenuto et al, 2018 , Deliens et al, 2018 , Holtgraves and Giordano, 2017 , Soroker et al, 2005 ). Further research has focused on the organisation and structure of conversations, which have yielded important insights on how human social interactions are organised in sequences (e.g., Kendrick et al, 2020 , Levinson, 2013 , Schegloff, 2007 ), where linguistic signs (words and sentences along with non-verbal communication, such as gestures) are used as a tool of communication to carry out linguistic actions, the so-called speech acts.…”
Section: Pragmatics and The Brainmentioning
confidence: 99%